A study on farmers' satisfaction and happiness after the land sale for urban expansion in India. (October 2021) - Kumar, Pankaj; Kumar, Parveen; Garg, Ramesh Kumar
Abstract: The study examines the farmers' satisfaction and happiness after the land sale for urban expansion of Gurugram, Haryana, India, under the "Development Plan 2031AD for Gurgaon-Manesar Urban Complex". Data was collected through a self-administrated survey questionnaire from 177 male farmers (168 valid) of sixteen villages whose land has been acquired or sold for urban expansion using convenience-cum-judgmental sampling technique. The data analysis was carried out using factor analysis and PLS-SEM (Partial Least Squares - Structural Equation Modeling). The study reveals that income source and spending pattern after the land sale, i.e., occupation and rental income, rise in spending on children education, household items, gadgets, car/sport utility vehicle, shopping, leisure, and social events positively and significantly affect farmers' satisfaction. The urbanization facets, i.e., urbanized lifestyle, nuclear families, basic facilities such as water, electricity, roads, and transportation, significantly affect farmers' satisfaction. The results also show that improved living status and compensation and its utilization for future financial enrichment after the land sale substantially influence farmers' satisfaction. On the contrary, social facilities, i.e., educational institutions, banking, hospitals, recreational facilities, and social costs, i.e., pollution and health concerns have no significant impact on farmers' satisfaction. Notably, this study finds that after the land sale, farmers' satisfaction significantly affects their happiness. Highlights: This study examines the determinants of farmers' satisfaction and happiness after the land sale. Data of male farmers of sixteen villages of Gurugram, India is analyzed using PLS-SEM. Income source and spending, urbanization aspect, and living status significantly impact farmers' satisfaction. Farmers' satisfaction significantly affects their happiness. The paper concludes with theoretical and policy implications.